The impact of genetic variants related to the fatty acid metabolic process pathway on milk production traits in Jersey cows - Sena Ardicli; Nursen Senturk; Berkay Bozkurt; Huseyn Babayev; Tuğçe Selvi; Stephen Skolnick; Hivdanur Ter; Beyza Aktas; Ayse Isık; Ozgur Toprak Ay; Ozge Ardicli; Ozden Cobanoglu (Animal Biotechnology, 2024)
The synthesis of fatty acids plays a critical role in shaping milk production characteristics in dairy cattle. Thus, identifying effective haplotypes within the fatty acid metabolism pathway will provide novel and robust insights into the genetics of dairy cattle. This study aimed to comprehensively examine the individual and combined impacts of fundamental genes within the fatty acid metabolic process pathway in Jersey cows. A comprehensive phenotypic dataset was compiled, considering milk production traits, to summarize a cow’s productivity across three lactations. Genotyping was conducted through PCR-RFLP and Sanger sequencing, while the association between genotype and phenotype was quantified using linear mixed models. Moderate biodiversity and abundant variation suitable for haplotype analysis were observed across all examined markers. The individual effects of the FABP3, LTF and ANXA9 genes significantly influenced both milk yield and milk fat production. Additionally, this study reveals novel two-way interactions between genes in the fatty acid metabolism pathway that directly affect milk fat properties. Notably, we identified that the GGAAGG haplotype in FABP3×LTF×ANXA9 interaction may be a robust genetic marker concerning both milk fat yield and percentage. Consequently, the genotype combinations highlighted in this study serve as novel and efficient markers for assessing the fat content in cow’s milk.